2006
DOI: 10.1002/dvdy.20858
|View full text |Cite
|
Sign up to set email alerts
|

Barhl1 is required for maintenance of a large population of neurons in the zonal layer of the superior colliculus

Abstract: The mammalian superior colliculus of the midbrain is a brainstem center that integrates sensorimotor signals involved in the control of orienting behaviors. Its structure is characterized by seven well-organized cellular and fibrous layers associated with distinct physiological properties. To date, however, little is known about the molecular bases governing the lamination, differentiation, and survival of superior collicular neurons. Barhl1 is a homeodomain transcription factor that has been demonstrated to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…Interestingly, deletion of the mouse Barhl1 gene, which encodes a BarH homeodomain protein, leads to progressive degeneration of cochlear hair cells and loss of many neurons from the zonal layer of the superior colliculus due to increased apoptosis in these regions (Li et al 2002;Li and Xiang 2006). These observations suggest that BarH homeodomain proteins may play a conserved role in promoting the survival of sensory neurons.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, deletion of the mouse Barhl1 gene, which encodes a BarH homeodomain protein, leads to progressive degeneration of cochlear hair cells and loss of many neurons from the zonal layer of the superior colliculus due to increased apoptosis in these regions (Li et al 2002;Li and Xiang 2006). These observations suggest that BarH homeodomain proteins may play a conserved role in promoting the survival of sensory neurons.…”
Section: Discussionmentioning
confidence: 93%
“…In the developing CNS, Barhl1 and Barhl2 are expressed in the superior and inferior colliculi of the midbrain, the cerebellar granule cells and precerebellar neurons of the hindbrain, and the dorsal interneurons of the spinal cord (4,19,20,26,31,32). Analyses of Barhl1-deficient mice have revealed a crucial role for Barhl1 in the migration and survival of cerebellar and precerebellar neurons and the long-term maintenance of superior collicular neurons as well (19,20). In the spinal cord, Barhl1 inactivation results in no appreciable change, yet gain-of-function studies have implied a role for Barhl2 in the differentiation of dorsal commissural sensory neurons (19,31,32), suggesting a likely functional redundancy between Barhl1 and Barhl2 during spinal neurogenesis.…”
mentioning
confidence: 99%
“…The targeted disruption of Barhl1 leads to hearing loss as a result of the age-related progressive degeneration of inner and outer hair cells in the organ of Corti (18), demonstrating a critical requirement for Barhl1 in the longterm maintenance of these sensory cells. In the developing CNS, Barhl1 and Barhl2 are expressed in the superior and inferior colliculi of the midbrain, the cerebellar granule cells and precerebellar neurons of the hindbrain, and the dorsal interneurons of the spinal cord (4,19,20,26,31,32). Analyses of Barhl1-deficient mice have revealed a crucial role for Barhl1 in the migration and survival of cerebellar and precerebellar neurons and the long-term maintenance of superior collicular neurons as well (19,20).…”
mentioning
confidence: 99%
“…Specifically, they found that the CES-1-like zinc-finger transcription factor, SLUG, controls PUMA transcription and that the transcription of SLUG in turn can be controlled by the oncoprotein, E2A-HLF (hepatic leukemia factor), which is composed of the DNA binding domain of the CES-2-like bZIP transcription factor HLF and the transactivation domain of the bHLH transcription factor E2A. Furthermore, mammalian or vertebrate homologs of C. elegans TRA-1 (GLI-like transcription factors) and CEH-30 (Barhl1, Barhl2) have been implicated in apoptosis regulation (Li et al, 2002Ruiz i Altaba et al, 2002;Offner et al, 2005;Li and Xiang, 2006). Although the relevant targets of these transcription factors in this context remain to be identified, one prediction is that they will include BH3-only genes.…”
Section: Discussionmentioning
confidence: 99%